Hvad hedder det på dansk? Polske studerendes brug af ordbøger mellem polsk og dansk - Ptaszynski, Marcin Overgaard; Sobkowiak, Mikołaj; Leroyer, Patrick (LexicoNordica, 2011)
The paper is a research study into how Polish students of Danish use dictionaries when translating from Polish into Danish and when writing texts in Danish. The methodology of the study relies on three assumptions: (1) the distinction between subjective and objective information needs, (2) the impact of educational level on lexicographic behaviour, (3) the differences in terms of users’ needs and their satisfaction during translation and free text production. By combining various data generating and gathering methods, the study provides an insight into differences between both kinds of needs. It uncovers the dictionary users’ objective needs and examines how their subjective needs are satisfied, i.e. which dictionaries are consulted, for what purposes, what determines their choice, and how useful they are.